Monitoring the Effectiveness of Energy Consumption for Old Buildings Using Data Gathered Through Temperature, Humidity, and Light Intensity - John Reigton Hartono; Ditdit Nugeraha Utama (Postgraduate, University of Mataram, 2025)
This research discusses the use of the Internet of Things in the monitoring of humidity, temperature, and light intensity conditions in a room that is connected to a mesh network. The objective of this research is to build a system that can monitor room conditions based on microcontrollers which are interconnected in a mesh network. The data are then displayed on a dashboard and categorized as either a comfortable or uncomfortable room based on existing standards. To ensure the accuracy of the system’s values, it is compared to commercial tools, then accuracy and precision are calculated. The system’s standard deviation for temperature is 0.12–0.19%, while its RMSE is 0.16–0.48%, and for humidity, the RMSE is 0.54–0.77%, with a standard deviation of 0.33–0.69%. For light intensity, with the outlier removed, the RMSE is 1.1–4.90% and the standard deviation is 0.79–2.76%. All these values are still comparable to the commercial tools’ accuracy listed in specification sheets. For packet loss, the system is run continuously for nine days, and at the end, the total data sent and data received at the server are calculated to count the differences. The packet loss after nine days and 777,600 data points is 0.00103–0.00193% from all six sensors used in the system.